2017
DOI: 10.1111/rec.12514
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and socioeconomic drivers of woody vegetation recovery in a human‐modified landscape in the Rio Grande basin (Colombian Andes)

Abstract: In the tropics, some agricultural lands are abandoned for economic or technical reasons, leading to the recovery of woody vegetation. Our research aimed to identify the main drivers of spontaneous recovery of vegetation in a basin located in the Colombian Andes. This was done by combining spatially explicit environmental and socioeconomic variables at landscape (e.g. distances to human settlements, to roads, and to forests and mean annual precipitation) and local scales (e.g. depth of the organic layer, soil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
(68 reference statements)
0
13
0
2
Order By: Relevance
“…As a consequence, the capacity of species to recover in these landscapes is lower (Arroyo‐Rodríguez et al., 2017; Martínez‐Ramos et al., 2016; Sansevero et al., 2017; Zermeño‐Hernández et al., 2015). In the absence of strong socioeconomic pressures for forest conversion, landscapes with higher ecosystem productivity, water availability, and favorable soil conditions are characterized by higher capacity of species to recover (Camelo et al., 2017; Rozendaal et al., 2019). Therefore, landscapes with favorable ecological and biophysical conditions and low socioeconomic pressures on land‐use change are crucial for increasing the chances of biodiversity recovery in second‐growth forests (Crouzeilles et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the capacity of species to recover in these landscapes is lower (Arroyo‐Rodríguez et al., 2017; Martínez‐Ramos et al., 2016; Sansevero et al., 2017; Zermeño‐Hernández et al., 2015). In the absence of strong socioeconomic pressures for forest conversion, landscapes with higher ecosystem productivity, water availability, and favorable soil conditions are characterized by higher capacity of species to recover (Camelo et al., 2017; Rozendaal et al., 2019). Therefore, landscapes with favorable ecological and biophysical conditions and low socioeconomic pressures on land‐use change are crucial for increasing the chances of biodiversity recovery in second‐growth forests (Crouzeilles et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on time series and shape-fitting analysis, a short permanence of regrowing forests and reforestation reversal was detected across Latin American secondary forests, compromising continental-scale carbon stores (Schwartz et al, 2020). Another remote sensing study at the Colombian scale detected woody vegetation recovery areas using Landsat data and found that recovery occurred near remnant forests and with distance from settlements and highlighted the need to evaluate socio-ecological conditions to define restoration approaches (Camelo et al, 2017). 3.…”
Section: Knowledge On Recovery Trends and Trajectories Of Degradedmentioning
confidence: 99%
“…While most studies were primary research including fieldwork, secondary research made up less than 15% of all studies, mostly as reviews 86 , 90 – 92 , reports 93 , 94 , model studies 88 , 95 , 96 and as five remote sensing studies 6 , 61 , 81 , 97 , 98 .…”
Section: The State Of Science In Tropical Mountain Restorationmentioning
confidence: 99%